Media Valorization of Feminine Beauty in Thai Public Discourse - Singhakowinta, Jaray (Kasetsart Journal of Social Sciences, 2014)
Contemporary society is often thought of being media-saturated as the mass media have increasingly become an integral part of modern ways of life. The media reinforce gender norms already being communicated by other social institutions through their representation or reconstruction of social reality. Despite legal and social recognition of gender equality, the media representation of both genders still reproduces stereotypical portrayals underlining biological and emotional differences between men and women. With the proliferation of beauty industries, the media reiterate the individual benefits of beautified bodies and encourage individuals to take control of their own beautification. This paper explores the Thai media’s representation of femininity in relation to the discursive embodiment of beauty discourse. It examines how the notion of beauty is defined and established in Thai public discourse, particularly in mainstream media texts. These texts are read to highlight power relations in the Thai media’s representation of modern Thai women. Two television commercial clips are selected for detailed visual analysis to illustrate how contemporary patriarchal values reinscribe feminine beauty as an essential, imperative commodity in Thailand’s capitalist economy. This paper underlines the connection between a patriarchal representation of beautiful women and the commodification of female bodies in valorizing a capitalist beauty discourse in Thai society.